Deep-Water Coral Banks: an Example from the “Calcare di Mendicino” (Upper Miocene, Northern Calabria, Italy) - MASTANDREA A.; MUTO F.; NERI C.; PERRI E.; RUSSO F.; PAPAZZONI, Cesare Andrea (Facies, 2002)
The “Calcare di Mendicino”, a mixed carbonate-siliciclastic informal unit of Late Tortonian-Early Messinian age, crops out extensively in the northwestern part of the Calabria. A good outcrop of this unit is located in the Scannelle quarry near Belsito (Cosenza). Five stratigraphical sections were studied to define the sedimentological and paleoecological setting. The carbonate body records the development of a deep-water coral bank characterized by a low-diversity constructor community of azooxanthellate scleractinian (Oculina and Dendrophyllia) and stylasterine hydrozoans colonies. Two main stages of bioconstruction growth can be distinguished: colony-thicket (floatstone facies) and coppice-bank (rudstone facies). Among the biostromal dwellers the more common are bryozoans, echinoids, benthic foraminifera, gastropods, and bivalves. Noticeable the extensive presence of planktonic foraminifera in the floatstone facies. The coral bank flourished within the aphotic zone, nourished by deep currents loading nutrient and siliciclastics.The lower part of the “Calcare di Mendicino” carbonate body has been affected by a widespread recrystallization, obliterating the primary geochemical characteristics of the carbonates. The diagenetic history, partly hidden, reveals three main stages: primary marine with isopachous fibrous cements, deep burial with cavities infilled by sparry calcite, and phreatic-meteoric with dog tooth cements. In the upper part of the carbonates, a pervasive dolomitization obliterated almost completely the sedimentary structures and the biofacies.